-1
1
undefined
Fill in the following: (Note that some answers may be used more than once.) Click Here for Help Video
�
0
=
x
0
=
−
(
�
)
0
=
−(x)
0
=
0
0
=
0
0
=
(
−
2
)
0
=
(−2)
0
=
(
�
⋅
−
2
)
0
=
(x⋅−2)
0=
DRAG & DROP THE ANSWER
−
1
−1
1
1
undefined
11 answers
are you sure
Yes, I am sure.
Fully simplify the following:
3
[
(
10
−
4
)
4
÷
2
]
3[(10−4)
4
÷2]
3
[
(
10
−
4
)
4
÷
2
]
3[(10−4)
4
÷2]
3[(10 - 4) * 4 ÷ 2]
First, calculate the value inside the parentheses:
10 - 4 = 6
Now substitute the result back into the expression:
3 * (6 * 4 ÷ 2)
Next, simplify within the brackets:
6 * 4 = 24
24 ÷ 2 = 12
Finally, multiply by 3:
3 * 12 = 36
Therefore, the fully simplified answer is 36.
First, calculate the value inside the parentheses:
10 - 4 = 6
Now substitute the result back into the expression:
3 * (6 * 4 ÷ 2)
Next, simplify within the brackets:
6 * 4 = 24
24 ÷ 2 = 12
Finally, multiply by 3:
3 * 12 = 36
Therefore, the fully simplified answer is 36.
are you sure?
Let's reevaluate the expression step by step:
3[(10 - 4) * 4 ÷ 2]
First, calculate the value inside the parentheses:
10 - 4 = 6
Now substitute the result back into the expression:
3 * (6 * 4 ÷ 2)
Next, simplify within the brackets:
6 * 4 = 24
24 ÷ 2 = 12
Finally, multiply by 3:
3 * 12 = 36
Yes, I am sure that the fully simplified answer is 36.
3[(10 - 4) * 4 ÷ 2]
First, calculate the value inside the parentheses:
10 - 4 = 6
Now substitute the result back into the expression:
3 * (6 * 4 ÷ 2)
Next, simplify within the brackets:
6 * 4 = 24
24 ÷ 2 = 12
Finally, multiply by 3:
3 * 12 = 36
Yes, I am sure that the fully simplified answer is 36.
Fully simplify the following:
20
+
2
−
4
20 + 2 −4 Click Here for Help Video
Fully simplify the following:
20
−
2
+
4
20−2+4
20
+
2
−
4
20 + 2 −4 Click Here for Help Video
Fully simplify the following:
20
−
2
+
4
20−2+4
Let's fully simplify the expressions:
1. 20 + 2 - 4:
Addition and subtraction are done from left to right:
20 + 2 = 22
22 - 4 = 18
Therefore, the simplified form of 20 + 2 - 4 is 18.
2. 20 - 2 + 4:
Subtraction (from left to right) and then addition:
20 - 2 = 18
18 + 4 = 22
Therefore, the simplified form of 20 - 2 + 4 is 22.
1. 20 + 2 - 4:
Addition and subtraction are done from left to right:
20 + 2 = 22
22 - 4 = 18
Therefore, the simplified form of 20 + 2 - 4 is 18.
2. 20 - 2 + 4:
Subtraction (from left to right) and then addition:
20 - 2 = 18
18 + 4 = 22
Therefore, the simplified form of 20 - 2 + 4 is 22.
Finding the missing side of the right triangle. Round your answer to the nearest tenth. Click Here for Help Video.
101010
292929
�=x=x=
101010
292929
�=x=x=
To find the missing side of a right triangle given the two other sides, we can use the Pythagorean Theorem which states that
a^2 + b^2 = c^2
Given the sides of the right triangle are 10, 29, and x, we can set up the equation:
10^2 + 29^2 = x^2
100 + 841 = x^2
941 = x^2
x = √941
x ≈ 30.7
Rounding to the nearest tenth, the missing side of the right triangle is approximately 30.7.
a^2 + b^2 = c^2
Given the sides of the right triangle are 10, 29, and x, we can set up the equation:
10^2 + 29^2 = x^2
100 + 841 = x^2
941 = x^2
x = √941
x ≈ 30.7
Rounding to the nearest tenth, the missing side of the right triangle is approximately 30.7.